Pathophysiological mechanisms of post-myocardial infarction depression: a narrative review - Garrels, Eric; Kainth, Tejasvi; Silva, Briana; Yadav, Garima; Gill, Gurtej; Salehi, Mona; Gunturu, Sasidhar (Frontiers in Psychiatry, 2023)
Myocardial infarction (MI) can have significant physical and mental consequences. Depression is a prevalent psychiatric condition after MI which can reduce the quality of life and increase the mortality rates of patients. However, the connection between MI and depression has remained under-appreciated. This review examines the potential connection between depression and MI by overviewing the possible pathophysiologic mechanisms including dysregulation of the hypothalamic-pituitary-adrenal axis and autonomic nervous system, coagulation system dysfunction, inflammation, environmental factors, as well as, genetic factors. Furthermore, depression can be an adverse event of medications used for MI treatment including beta-blockers, statins, or anti-platelet agents. The need for early detection and management of depression in patients with MI is, therefore, crucial for improving their overall prognosis. Adherence to treatments and regular follow-up visits can ensure the best response to treatment.